Analysis of the Implementation of the Tahfizh Program at State Islamic Senior High School 1 Pasaman - Wardiyatun Musfiroh; M. Zuhri; Wilrahmi Izati; Elis Marini; Achyar Rochman; Afrihaldi Afrihaldi (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
The development of the tahfizh program in schools has not been fully successful in achieving its targets, and many have even failed. This study aims to analyze how the implementation of the tahfizh program is carried out at Madrasah Aliyah Negeri 1 Pasaman. This study uses method qualitative with approach descriptive. Data sources were taken from twelve informants through in-depth interviews selected using the snowball sampling technique , all informants were active teachers and students at Madrasah Aliyah Negeri 1 Pasaman in the 2023/2024 academic year. The results of the analysis show i) the planning of the tahfizh program at Madrasah Aliyah Negeri 1 Pasaman, such as the Learning Implementation Plan (RPP) exists and is made at the beginning of each semester with the K13 type. ii) the implementation of the tahfizh program at Madrasah Aliyah Negeri 1 Pasaman is carried out once a week with a time allocation of two hours outside of structured class hours. iii) evaluation of the implementation of the tahfizh program is carried out at the end of each semester and is only carried out by the curriculum representative and tahfizh teacher. iv) related to the obstacles that occur in the implementation of the program consisting of student factors, teacher factors, environmental factors, time factors, and infrastructure factors. The results of this study can be used as initial data for subsequent researchers in examining this problem in different contexts and issues.